Some Methods of Foreign Language Teaching in Distance Education (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The article discusses the use of innovative technologies in the process of teaching a foreign language, using the example of English in distance education. Particular attention is paid to such means as podcasts, project technology, and the method of working on stations. Also, special attention is paid to the use of innovative technologies, which makes the educational process more effective, increases students’ motivation to learn a foreign language and contributes to the formation of universal and professional competencies. The important role of such pedagogical techniques as self-assessment and reflection is noted for the enrichment and qualitative transformation of the educational process.